Impact of 5 days of sprint training in hypoxia on performance and muscle energy substances - Kasai, N.; Kojima, C.; Sumi, D.; Takahashi, H.; Goto, K.; Suzuki, Y. (International Journal of Sports Medicine, 2015)
The present study was designed to determine the effect of 5 consecutive days of repeated sprint training under hypoxia on anaerobic performance and energy substances. Nineteen male sprinters performed repeated sprints for 5 consecutive days under a hypoxic (HYPO; fraction of inspired oxygen [FiO2], 14.5%) or normoxic (NOR; FiO2, 20.9%) condition. Before and after the training period, 10-s maximal sprint, repeated sprint ability (5×6-s sprints), 30-s maximal sprint, and maximal oxygen uptake (VO2max) tests were conducted. Muscle glycogen and PCr contents were evaluated using carbon magnetic resonance spectroscopy (13C-MRS) and phosphorus magnetic resonance spectroscopy (31P-MRS), respectively. The HYPO group showed significant increases in power output during the 10-s maximal sprint (P=0.004) and repeated sprint test (P=0.004), whereas the NOR group showed no significant change after the training period. Muscle glycogen and PCr contents increased significantly in both groups (P<0.05, respectively). However, relative increases were not significantly different between groups. These findings indicated that 5 consecutive days of repeated sprint training under hypoxic conditions increased maximal power output in competitive sprinters. Furthermore, short-term sprint training significantly augmented muscle glycogen and PCr contents with little added benefit from training in hypoxia.